A decreased abundance of clostridia characterizes the gut microbiota in eosinophilic esophagitis. Issue 20 (24th October 2019) - Kashyap, Purna C.; Johnson, Stephen; Geno, Debra M.; Lekatz, Heather R.; Lavey, Crystal; Alexander, Jeffrey A.; Chen, Jun; Katzka, David A.
Abstract: Abnormalities in the gut microbiome are associated with suppressed Th2 response (Belizario et al., 2018 Mediators Inflamm . 2018:2037838) and predisposition to atopic disease such as asthma and eczema. We investigated if this applies to eosinophilic esophagitis (EoE). Stool bacterial DNA was extracted and followed by 16S rRNA amplification from 12 patients with eosinophilic esophagitis and 12 controls. Alpha‐ and beta‐diversity were analyzed. Only two patients had asthma or atopy and one patient was on budesonide. No patients were on PPIs. Patients with EoE had lower gut microbiota alpha diversity (species richness, P = 0.09 ; Shannon index, P = 0.01). The microbial composition was distinct as evidenced by significantly different beta diversity ( P = 0.03) when compared to healthy controls. There were also significant differences in relative abundance at multiple taxonomic levels when comparing the two communities; at the phylum level, we observed a marked decrease in Firmicutes and increase in Bacteroidetes and at the order and family level there were significant decreases in Clostridia and Clostridiales in patients with EoE ( q ≤ 0.1). We conclude that there are significant differences in microbial community structure, microbial richness, and evenness and a significant decrease in taxa within the Clostridia in patients with EoE. Our data suggest that Clostridia based interventions could be tested as adjuncts to current therapeutic strategies in EoE. Abstract : We investigated if abnormalities in the gut microbiome associated with suppressed Th2 response are present in patients with eosinophilic esophagitis. Patients with EoE had lower gut microbiota alpha diversity and a distinct microbial composition as evidenced by significantly different beta diversity, marked decrease in Firmicutes, Clostridiales and an increase in Bacteroidetes. We conclude that there are significant differences in microbial community structure, microbial richness, and evenness and a significant decrease in taxa within the Clostridia in patients with EoE. Our data suggest that Clostridia based interventions could be tested as adjuncts to current therapeutic strategies in EoE.